Relevance of Content Standards to Learners’ Needs in Community Education at PKBM Garuda Giver Pekanbaru - Muhammad Rizki; Rahmat Fahmi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the relevance of content standards to the needs of learners in community education at PKBM Garuda Giver, Pekanbaru. Using a qualitative approach with in-depth interview method involving the Head of PKBM Garuda Giver as the key informant, this study finds that relevant content standards constitute the primary foundation for effective and impactful learning within the community. The discussion begins with a conceptual review of content standards in non-formal education, then sharpened through analysis of actual practices at PKBM Garuda Giver. The institution has proven to operationalize content Package A ,Package B and C. The curriculum is developed from the actual needs and problems of learners, not from administrative templates. Resulting in meaningful learning processes and sustainable impact on learners' lives..